Schools’ Strategies in Enhancing Students’ Self-Efficacy Related to English Language Skills - Noka Sholehiya; Siminto; Akhmad Ali Mirza (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates school strategies in enhancing students’ self-efficacy related to English language skills at SMP Negeri 2 Palangka Raya. The research problem arises from the observation that many junior high school students experience low self-efficacy and hesitation when learning English, which affects their participation and language performance. Therefore, this study aims to examine how school programs are implemented to enhance students’ self-efficacy, how these programs are carried out in the classroom, and what obstacles the school encounters in improving students’ self-efficacy. This research employed a qualitative approach using a case study method. Data were collected through interviews with the school principal, English teachers, and students, as well as through observation and documentation. The findings reveal that the school implements several strategic programs to enhance students’ self-efficacy, including the “Student Talent Showcase” program, which provides opportunities for public speaking and English storytelling, teacher participation in professional development forums, and specialized mentoring for English competitions. At the classroom level, teachers apply role-play activities, peer modeling, culturally responsive teaching, and supportive feedback to build students’ confidence in using English. However, several obstacles remain, particularly internal psychological barriers such as fear of making mistakes, lack of intrinsic motivation, and self-doubt among students with low self-efficacy. External factors, such as differences in learning support outside school, also influence students’ self-efficacy. The findings contribute to understanding how institutional programs and classroom strategies can support the development of students’ self-efficacy in English language learning.